Doing the plane dynamic elasto-plastic problem by the method of elastic root - Bich, Nguyen Dang (Vietnam Journal of Mechanics, 1985)
In this paper, the method of clastic root used to answer the plane dynamic elasto plastic problem, for the half of plane made by material according to the theory of small elasto-plastic deformation, on the boundary supporte1 degree loading of motion with over sound speed, root in the first -step given analytical form.